Fractures of the manubrium sterni: treatment options and a possible classification of different types of fractures - Schulz-Drost, Stefan; Krinner, Sebastian; Oppel, Pascal; Grupp, Sina; Schulz-Drost, Melanie; Hennig, Friedrich F.; Langenbach, Andreas (Journal of Thoracic Disease; Vol 10, No 3 (March 31, 2018): Journal of Thoracic Disease, 2018)
Background: Sternum fractures are mostly located on the sternal corpus, seldom on the manubrium. Fractures of the sternal manubrium are, however, more frequently associated with severe concomitant injuries of thoracic organs, and therefore deserve special attention. In addition, in its function as a capstone in between the anterior chest wall and the shoulder girdle, it is exposed to a multiplicity of forces. Therefore the questions arise what types of fractures are observed in today’s clinical practice, how to classify them and which treatment options are available. This study reports on different types of fractures which involve the manubrium sterni. Methods: Between January 2012 and October 2014, data was collected from all severely injured patients (ISS ≥16), which received a CT scan of the thorax in our Level-I-Trauma Center and retrospectively analyzed concerning sternal fractures. Fracture type, collateral injuries, age, and information about the circumstances of the accident were noted. Results: Of 890 evaluable patients, 154 (17.3%) had a fracture of the sternum and 23 (2.6%) of the manubrium. Fractures of the manubrium appeared in following types: A-type—transverse fracture (n=11) in 1st intercostal space by direct blunt trauma or flexion of the torso with sagittal instability; B-type—oblique fracture (n=9) by seat belt injury with rotatory instability; C-type—combined, more fragmentary fracture (n=3) by direct blunt trauma with simultaneous flexion of the torso and multi directional instability. Fractures only little dislocation were treated conservatively, and unstable fractures were surgically stabilized (n=10). Conclusions: In summary, three main types of fractures could be found. A-type fractures were stabilized with a longitudinal plate osteosynthesis and B-type fractures with transverse positioned plates. To treat complex C-type fractures, plates with a T- or H-form could be a good solution. Level of evidence: Level III retrospective prognostic cohort study.